Validation of the Italian version of the Eating-Related Eco-Concern Questionnaire: insights into its relationship with orthorexia nervosa - Tecuta, Lucia; Casu, Giulia; Tomba, Elena (Frontiers in Psychology, 2024)
Urgent calls for research on the relationship between climate change concerns and eating disorder risk have been made. This study aimed to validate an Italian version of the Eating-Related Eco-Concern questionnaire (EREC), a brief unidimensional measure of eating behaviors related to eco-concern. 663 adults (85% females, mean age 37 ± 12 years) completed the EREC, Climate Change Worry Scale (CCWS), Eating Disorder Examination-Questionnaire (EDE-Q), Eating Habits Questionnaire for orthorexia nervosa symptoms (EHQ-21), and questions on dietary habits and motivations, and past experiences of extreme climate events. Confirmatory factor analysis results indicated that the original one-factor model showed acceptable fit to the data after including the error covariation between two pairs of items. Internal consistency was adequate, and EREC scores correlated positively and strongly with CCWS scores. Participants scored significantly lower in EREC than in CCWS, indicating greater climate-related concerns in general terms than relating specifically to eating. While EREC was unrelated to EDE-Q scores, weak-to-moderate correlations were observed with EHQ-21 subscale and total scores. Proenvironmental and/or ethical reasons for current diet and personal experience of extreme climate events were associated with significantly higher EREC scores. The Italian EREC appears to be a valid and reliable tool for the screening of eating-related concerns and behaviors related to climate change. Ecological concerns may represent a healthy adaptive response, but the EREC can serve as a valuable tool to identify individuals whose eating behaviors related to eco-concern might warrant further clinical attention due to potential risks of developing rigid or unhealthy patterns.